Antigen-Specific CD4+ T Cells Exhibit Distinct Kinetic and Phenotypic Patterns During Primary and Secondary Responses to Infection - Malhotra, Deepali; Burrack, Kristina S.; Jenkins, Marc K.; Frosch, Anne E. (Frontiers in Immunology, 2020)
Although CD4+ T cell memory is a critical component of adaptive immunity, antigen-specific CD4+ T cell recall responses to secondary infection have been inadequately studied. Here we examine the kinetics of the secondary response in an important immunological model, infection with attenuated Listeria monocytogenes (Lm). We identify CD4+ T cell subsets that preferentially expand during a secondary response and highlight the importance of prime-boost strategies in expanding and maintaining antigen-specific, tissue-resident memory CD4+ T cells. Following intravenous infection with an attenuated strain of Lm, we found that total antigen-specific CD4+ T cells responded more robustly in secondary compared with primary infection, reaching near-peak levels in secondary lymphoid organs and the liver by three days post-infection. During the secondary response, CD4+ T cells also contracted more quickly. Primary Lm infection generated two main classes of effector cells: Th1 cells that assist macrophages and T follicular helper (Tfh) cells that aid B cells in antibody production. We found that during the secondary response, a population of Ly6C+ Tfh cells emerged in secondary lymphoid organs and was the basis for the skewing of this response to a Tfh phenotype. Deletion of T-bet in T cells precluded development of Ly6C+ Tfh cells, but did not alter anti-Lm antibody responses. Moreover, during recall responses, CD49a+ Th1 cells preferentially expanded and accumulated in the liver, achieving a new set point. Parabiosis experiments indicated that, in contrast to Tfh cells and most splenic Th1 cells, the majority of CD49a+ Th1 cells in the liver were tissue resident. Overall, these data demonstrate a robust secondary CD4+ T cell response that differs in kinetics and composition from the primary response and provide insight into targets to enhance both peripheral and tissue-resident CD4+ T cell responses.